Covid-19: Prayers Performance of Medical Team Without Ablution and Tayammum Based On Four Madhab Fiqh - Hudzaifah Achmad Qotadah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractOne of the main pillars of Islam is salat, wherein obliging salat, Allah SWT raised Prophet Muhammad SAW directly to the heavens through Isra Mi’raj. Five daily prayers are obligatory duties that must be performed by every Muslim as proof of devotion, obedience, and submission to His command with its requirements and pillars. The essence of salat cannot only be seen in practice but also on its process, such as wudu. Wudu is a procedure to purify the body with water. Wudu is one of the requirements for a valid salat, which is an obligation for every Muslim. Islam is filled with blessings and ease (rukhsah), given by Allah SWT to His Muslim servants. If one cannot perform wudu with water, then Allah SWT gave rukhsah, which is tayammum. A problem occurs if a Muslim unable to perform both wudu and tayammum, Which the COVID-19 healthcare worker is experiencing recently. This article is intended to research the rules in performing salat without wudhu or tayammum for COVID-19 healthcare workers based on four madhhab fiqh. In this research, the researcher uses a full qualitative method and documentation related to the topic of this research, which then will be analyzed descriptively.Keywords: Salat, Wudhu, Tayammum, COVID-19, Madhab. AbstrakSepertimana diketahui bahawa salah satu daripada pokok ajaran agama ialah shalat dimana dalam mewajikan ibadah shalat, Allah SWT langsung mengangkat Nabi Muhammas SAW ke langit melalui peristiwa Isra Mi’raj. Shalat fardhu yang lima waktu merupakan ibadah maktubah yang wajib diamalkan oleh setiap hamba-Nya yang muslim sebagai bukti daripada sebuah ketaatan, kepatuhan serta ketundukan pada perintah-Nya SWT dengan syarat dan rukun yang melekat di dalamnya. Esensi ibadah shalat bukan hanya sekedar terihat dari sisi pelaksanaan shalatnya akan tetapi dilihat dari sisi mulai prosesnya ibadah shalat itu sendiri seperti berwudhu. Wudhu merupakan salah satu cara menyucikan anggota tubuh dengan air dimana wudhu menjadi salah satu syarat sahnya ibadah shalat yang mesti dilakukan oleh setiap umat muslim. Agama Islam penuh dengan keberkahan serta kemudahan (rukhsah) yang diberikan Allah SWT kepada hamba-Nya yang muslim dimana apabila berhalangan berwudhu dengan air maka Allah SWT memberikan rukhsah berupa bertayammum. Namun, bagaimana jika seorang muslim berhalangan dalam melakukan keduanya baik wudhu mahupun tayammum seperti halnya yang dirasakan baru-baru ini oleh para petugas medis COVID-19. Artikel ini bertujuan untuk meneliti bagaimana hukum melaksanakan ibadah shalat tanpa berwudhu mahupun bertayammum bagi para petugas medis COVID-19 berdasarkan kepada pandangan-pandangan madhah fiqih. Metode yang digunakan penulis dalam penelitian ini ialah dengan menggunakan metode kualitatif penuh serta data dokumentasi yang terkait dengan topik kajian penelitian ini, kemudian dianalisis secara deskriptif.Kata-kata kunci: Shalat, Wudhu, Tayammum, COVID-19, Madhab.